The psychological science of money - Aarts, Henk; Bijleveld, Erik (Springer New York, 2014)
Money. The root of all evil? Arguably. Essential to our lives? Certainly. A main driver of human thought, emotion, and action? Absolutely--and psychology and its related fields are getting closer to understanding its complex role in human behavior and in society.    The Psychological Science of Money brings together classic and current findings on the myriad ways money affects brain, mind, and behavior to satisfy not only our needs for material gain, but also for autonomy and self-worth. Leading experts trace the links between early concepts of value and modern symbolic meanings of wealth, in addition to identifying the areas of the human brain that together act as its financial center. This cross-disciplinary analysis helps clarify the neuroscience behind pathological gambling, the critical role of time in financial decisions, and the impact of money on diverse personal activities and interpersonal relationships. Included in the coverage:   Materiality, symbol, and complexity in the anthropology of money. The (relative and absolute) subjective value of money. Conscious and unconscious influences of money: two sides of the same coin? A life-course approach to dealing with monetary gains and losses Motivation and cognitive control: beyond monetary incentives. An integrative perspective on the science of getting paid. The psychological science of spending.   The unique role of money in society makes The Psychological Science of Money a singularly fascinating resource with a wide audience among social psychologists, industrial and organizational psychologists, economists, sociologists, anthropologists, and public policymakers.